1975
DOI: 10.1037/0012-1649.11.6.667
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal orientations and cognitive functioning among adolescents.

Abstract: The purpose of this study was to examine the pattern of relations of attitudinal orientations to cognitive functioning in a sample of Israeli seventh-grade students (N = 950). Following Coleman et al.'s 1966 study, attitudinal orientations were represented by measures of locus of control, self-concept, and educational aspirations. Multiple regression analyses showed that 18.1% to 31.6% of the total variance in four measures of cognitive functioning was associated with attitudinal orientations, while only 10.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1976
1976
1983
1983

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…But the correlational nature of the design does not allow the disentanglement of the reciprocity of influence between student achievement and teacher perception of attitudes (30,35,36). The moderate relations between locus of control and performance scores replicate a number of previous studies (8,16,31).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…But the correlational nature of the design does not allow the disentanglement of the reciprocity of influence between student achievement and teacher perception of attitudes (30,35,36). The moderate relations between locus of control and performance scores replicate a number of previous studies (8,16,31).…”
Section: Resultssupporting
confidence: 69%
“…There is considerable evidence that students taught by the PSI approach perform better on examinations covering course content than students taught by a lecture approach (2 , 8, 9). Studies have also shown that student attitudes are more favorable toward PSI than toward lecture·type courses (6,11,16).…”
Section: Discussionmentioning
confidence: 97%